Quantum suppression of antihydrogen formation in positronium-antiproton scattering. Issue 1 (December 2017) - Kadyrov, A.; Bray, I.; Charlton, M.; Fabrikant, I.
Abstract The interaction of antiprotons with low-energy positronium atoms is a fundamental three-body problem whose significance is its utility for formation of antihydrogen. Particular importance resides in understanding processes involving excited positronium states. Until recently such studies were performed using classical techniques. However, they become inapplicable in the low-energy domain. Here we report the results of comprehensive quantum calculations, which include initial excited positronium states with principal quantum numbers up ton i  = 5. Contrary to expectation from earlier work, there are only muted increases in the cross-sections for antihydrogen formation forn i  > 3. We interpret this in terms of quantum suppression of the reaction at higher angular momenta. Furthermore, the cross-sections for elastic scattering are around two orders of magnitude higher, which we attribute to the degeneracy of the positronium states. We outline some experimental consequences of our results. The intriguing behaviour of positronium scattering has its role in antimatter studies. Here the authors have predicted the quantum suppression of the cross-section for antihydrogen formation in positronium scattering with antiprotons, by including the excited states and using convergent close-coupling calculations.